The application of the boundary elemenl method lo the study of 2D subsonic lifting flow past smooth profiles - Carabineau, A. (Archives of Mechanics, 1996)
In this paper, using the Imai-Larnla-Iacob method based on the asymptotic expansion of the complex velocity potential with respect to Chaplygin's number M0, we study the subsonic steady 2D lifting flow around arbitrary smooth obstacles. Reducing the investigation of the compressible flow to a sequence of boundary value problems for the Laplace equation, we use the boundary element method in order to calculate the distribution of fluid speed and pressure coefficients on the obstacle. A comparison between the results obtained numerically and analytically for the circular obstacle shows a very good agreement.